Comparação das técnicas de ativação convencional e cimentação para a união do intermediário ao implante friccional: análise da adaptação marginal e resistência à tração - Ramos, Fabiola Nascimento (2017)
Loosening implant connections is related to the gaps of the implant-abutment (IA) connections. The objective of this study was to analyze the IA connection frictional as well as the union force of this connection when activation is increased cementation. An in vitro laboratory experiment was performed by one operator, two groups of IA mounts were evaluated means by obtaining images with a stereoscopic loupe. Nine implants were divided into two groups: Group I (GI), in which received conventionally activated attachment ball (Kopp®) prostheses and Group II (G II), in wich dual resin cement (Variolink II®) was added prior to the activation of the abutment. For the analysis of gaps and tensile strength test, Shapiro-Wilk test and F test were used, followed by t test (p <0.05).There was difference between the groups in relation to the gaps; even though the dimensional increase of the gaps, the resist the traction was superior. The cementation suggested to have influenced the increase of the union strengh between the implant-abutment connection, even with the increase of the gaps.